(untitled) (Journal of Information Technologies in Education (ITE), 2010)
An approach to the allocation of teaching load at the university, which is based on the simultaneous integration of several disciplines teachers. It is shown that the problem reduces to systems of nonlinear Boolean equations and proposed rank method for its solution.